2015
DOI: 10.5114/pg.2015.48994
|View full text |Cite
|
Sign up to set email alerts
|

Elastography in pancreatic solid tumours diagnoses

Abstract: IntroductionPancreatic solid tumour diagnoses remain a challenge for modern medicine. However, using endosonography together with elastography helps to examine the elasticity of tissues and therefore may allow definition of the nature of pancreatic tumours.AimTo evaluate the usefulness of elastography with the strain ratio method and quantitative evaluation of pancreatic solid tumours.Material and methodsA total of 54 patients with pancreatic solid tumours were treated with ultrasound endosonography with fine-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…In one patient with fi ndings compatible with chronicity, a higher stiffness was observed, with bigger and more frequent reddish areas. Although in the present study there was no suspicion of neoplastic lesions, it is suspected that stiffness of these tissues may be higher than in chronic lesions, which might aid in the differential diagnosis of chronic pancreatitis and pancreatic neoplasms, which is still challenging [20]. Further studies are necessary in order to contribute for diagnosis of these alterations.…”
Section: Resultsmentioning
confidence: 60%
“…In one patient with fi ndings compatible with chronicity, a higher stiffness was observed, with bigger and more frequent reddish areas. Although in the present study there was no suspicion of neoplastic lesions, it is suspected that stiffness of these tissues may be higher than in chronic lesions, which might aid in the differential diagnosis of chronic pancreatitis and pancreatic neoplasms, which is still challenging [20]. Further studies are necessary in order to contribute for diagnosis of these alterations.…”
Section: Resultsmentioning
confidence: 60%
“…[17] Since carcinomas were found to be stiffer than adjacent normal tissues and studies reported that histologically different tumors may display different elasticity patterns according to tissue architecture, [7,10] this technique has been successfully applied to differentiate focal lesions of testis, breast, prostate, pancreas and liver. [14,[18][19][20] Recently, shear wave elastography (SWE) which combines B-mode image with color-coded US generating a quantitative image SWE (kPa) of the tissue stiffness started to be used to exhibit different hardness among different tissue regions in real-time conditions. [21] With the use of SWE, different elasticity values dependent on testicular volume and functional properties have been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…SWE is a widespread imaging tool used in the assessment of liver fibrosis and evaluation of breast, thyroid, prostate and testes nodules. However, it was previously never used to assess testicular stiffness with respect to the issue of fertility 20‐24 . Recently, the diagnostic role of SWE in detecting different elasticity values depends on testicular volume and functional properties as previously demonstrated 25 .…”
Section: Discussionmentioning
confidence: 99%